Patterns of Multiple Intelligences among High School Students in Misan Governorate According to The (TEEN-MIDAS) Scale and Their Relationship to Achievement - misanjas, misanjas; Mahdi Siker, Haneen; Abdul-Muhsin, Ahmed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The study aims to identify the multiple intelligence patterns among high school students in Misan Governorate according to the (TEEN-MIDAS) scale and their relationship to the achievement. The researcher followed the descriptive survey method and the descriptive correlational method, where the research sample consisted of (200) male and female students from Maysan Governorate. The research sample was selected by a stratified random method. The study tools consisted of the TEEN-MIDAS scale for multiple intelligences. The researcher carried out the necessary statistical processing to confirm the psychometric properties of the study tool and to verify the validity of the hypotheses. The results were as follows: 1- Social intelligence ranked first among middle school students in Maysan Governorate 2-The results showed a high correlation between the multiple intelligence patterns of middle school students in Maysan Governorate according to the variable (gender and achievement) 3- The results also showed that there were differences between students (scientific, literary, industrial, and commercial) in the types of multiple intelligences. Based on the results of the research, the researcher recommends adopting the multiple intelligence scale (Teen-Midas) in the future to evaluate students who will move from middle school to high school in order to direct them to the specialization that suits their abilities and abilities.